Static Output Feedback Control of Continuous Time Matrix Lyapunov and Sylvester Systems - Rompicharla, L.N. Charyulu.; Putcha, Venkata Sundaranand; Deekshitulu, G.V.S.R. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper deals with the linear matrix inequality (LMI) conditions for output feedback control problems defined by continuous matrix systems. The solution of nonlinear matrix inequality obtained in the Lyapunov function approach for the stabilization of matrix Lyapunov and Sylvester systems is obtained in terms of the solutions of corresponding linear matrix inequalities (LMIs). The established results are based on sufficient conditions since they are dependent on the state-space representation used for describing the continuous time matrix Lyapunov and Sylvester systems. Linear Matrix Inequalities (LMI) are constructed to establish sufficient conditions for the continuous time matrix Lyapunov and Sylvester systems. The established conditions demonstrated by a numerical examples.